Stabilization of Clay Soil in Relation to CBR Value using Palm Oil Fuel Ash (POFA) in Flood-Prone Areas - Akbar Kurnia; Fithriyah Patriotika; Rizka Joniva Sari; Majid Maulana (Universitas Negeri Padang, 2025)
Oil is a crucial element in supporting the structural integrity of buildings. However, the rapid development of infrastructure has led to a reduction in the availability of land with favorable soil conditions, forcing many constructions to be built on less stable soils. The clay soil in Tunggul Hitam, Padang City, has a low bearing capacity, exhibits high shrink-swell behavior, and loses stiffness when wet, which may result in damage to roads and foundation structures. To address this issue, chemical stabilization was carried out using palm shell ash as an additive. This research aims to analyze the California Bearing Ratio (CBR) value of clay soil in the Tunggul Hitam area of Padang City by incorporating palm shell ash in varying proportions of 0%, 4%, 8%, 12%, and 16%. The soil types used in this study were Organic Clayey Silt and Silty Clay (OL). The tests included determining the physical and mechanical properties of the soil, such as sieve analysis, specific gravity, plastic limit, liquid limit, and CBR value. The CBR tests were conducted after soaking the samples for four days. The results showed that the CBR value of the untreated soil (soaked, 65 blows) was 6.1%, which increased to 31.512% at a 16% mixture ratio. This 25% improvement in CBR value indicates that palm shell ash is effective as a stabilizing agent for enhancing the engineering properties of clay soil in the study area